Sharecropping and Production Risk of Rice Farming - Redini Shaqilha Zakaria; Dwi Rachmina; Netti Tinaprilla (Agro Bali : Agricultural Journal, 2023)
Sharecropping is a form of cooperation between landowners and tenants. Two types of sharecropping systems for rice farming in Bone District, South Sulawesi, impact income and production risks. This study aims to (1) analyze the implementation of the sharecropping system and (2) analyze income and production risk. This study used primary data from 117 Berebbo sub-district, Bone district farmers. Data were analyzed using income analysis and production risk. The results showed that the sharecropping system has been implemented traditionally according to customs and is not guided by Law No. 2 of 1960 about the sharecropping system. The sharecropping system has survived to this day because, in addition to improving the economy, it also strengthens farmers' social relations through honesty, trust, and helping each other.  There are two types of sharecropping of grain; type 1 is 1:2, and type 2 is 1:1. In type 1, the landowner only provides the land, while in type 2, the landowner provides the land and shares the cost of fertilizers, pesticides, and transportation. The profit of farming using type 2 is higher than type 1, but the risk level of type 2 is also higher than type 1. But the landowner gets a higher profit than tenants because the output distribution is grain without considering farming costs. The output should share the profits to provide justice for both parties. The results of this study can become literature for future researchers to study production risks in sharecropping systems.